Design and development of driving system for disabled driver - Abdullah, Kassim Abdulrahman; Mohamed Ali, Jaffar Syed; Tuan Kamaruddin, Tengu Nordayana; Md Saufi, Syaira Jihan (2010)
Being able to drive a car is a major step towards independence for people with disabilities, but the conventional driving system installed in a car is not equipped with the utility for the disabled driver to drive the vehicle. Thus this paper presents the development of a new driving system for a disabled driver. In this work modification was made to the existing conventional systems by using hand-operated mechanisms for braking and acceleration systems, while for the steering system, steer-by-wire concept was applied